GDNF receptor GFRα1 is necessary for the maintenance of dopaminergic neurons in the adult substantia nigra - Alvaro Carrier-Ruiz; Annika Andersson; Diana Fernández-Suárez; Carlos F. Ibáñez (PLoS ONE, 2025)
GFRα1 and Ret are the two necessary components of the receptor for GDNF, a neurotrophic factor discovered in the early 1990’s for its ability to support the survival of midbrain dopaminergic neurons, including those in the substantia nigra (SN) that project to the dorsal striatum (dSTR) and degenerate in Parkinson’s Disease. Several GDNF clinical trials have been conducted to date with mixed results. Despite the physiological and clinical importance of this signaling system, whether any of its components are required for the maintenance of adult SN neurons has not yet been elucidated. In this study, we first analyzed postnatal expression patterns of Gfrα1 and Ret in the SN and established that mRNA levels peak at mouse postnatal day 15 (P15), stabilizing after P30. Using Tamoxifen-induced deletion of Gfrα1 at 3 months of age, we found that GFRα1 is required for the maintenance of a subset of adult SN dopaminergic neurons. FluoroGold tracing of SN axons from the dSTR in mutant mice revealed that ablation of GFRα1 preferentially affects the subset of GFRα1-expressing neurons that project to the STR. In addition to the well-known neuroprotective functions of GDNF/GFRα1/RET signaling, our results establish a physiological requirement of the GFRα1 component of this neurotrophic system for the continuous maintenance of SN dopaminergic neurons in the adult brain.